The Effectiveness of Acupressure Therapy to Reduce Nausea and Vomiting in Colorectal Cancer Patients Undergoing Chemotherapy: Case Study - Mega Apriyanti; Anggri Noorana Zahra (Essential English Grammar, 2022)
Chemotherapy have side effect for colorectal cancer patients such as anemia, leukopenia, neutropenia, thrombocytopenia, heart and skin disorders, diarrhea, mucositis, nausea, vomiting, and hypersensitivity reactions. Themost common side effects in patients undergoing chemotherapy cycles are Nausea and vomiting. It common effect impact patient's quality of life. The purpose of this article is to analyze nursing interventions in a 38-year-old woman whileundergoing the 3rd cycle of chemotherapy with the application of acupressure therapy to reduce nausea and vomiting.This article uses the case study method using the Visual Analog Scale (VAS) instrument to measure the level of nauseabefore and after being given acupressure intervention. The massage point area to suppress or reduce nausea and vomiting is at points P6 and ST36. This acupressure technique intervention was given for 5 days of treatment. Based on this, the intervention of acupressure techniques at points P6 and ST36 is effective to reducing complaints of nausea in cancer patients undergoing chemotherapy. This study recommends acupressure as a non-pharmacological intervention that can be implemented in patients with chemotherapy effect which nausea and vomiting in patients undergoing chemotherapy at the hospital